The Relationship Between the Roles of Teachers’ Effectiveness and Language Activities Utilization in English Instruction at Higher Education Institutions in Southern Laos - SORKEOMANY, Bounsong; PHONETHEP2, Jorky; MAHAPHOM2, Somphien; KEOKASEUMSOUK2, Saleumsai (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study identifies three key objectives were to: (1) investigate the effective roles of English Language Teaching (ELT) teachers in English courses, (2) identify the English language activities implemented in these courses, and (3) examine the relationship between effective ELT teachers' roles and their application of ELT activities. A purposive sampling technique, based on Krejcie and Morgan's formula, was utilized to select 78 EFL teachers and 365 English major students. Data were collected through a mixed-methods approach, employing a survey questionnaire and focus-group interviews. Statistical analyses, including frequency, mean, standard deviation, and Pearson correlation coefficients were conducted to interpret the data. The findings revealed that the highest mean scores were associated with the 'Cognitive Roles' of EFL teachers, indicating a strong foundation for effective teaching as perceived by participants. However, lower scores in the 'Neutral' category suggested a gap in utilizing video and audio strategies, pointing to potential limitations in integrating technology into instruction. Additionally, EFL teachers' managerial roles received positive evaluations, with most indicators rated at the 'Extremely Agree' level. Nonetheless, some indicators also fell into the 'Neutral' range, highlighting areas for improvement. The analysis of EFL teachers' 'Affective Roles' showed generally strong capabilities; however, similar lower scores in the 'Neutral' range indicated further areas for development. Furthermore, the Classroom Activities Inventory indicated that "Meaning-focused interactive activities" received the highest mean scores, and followed by the use of ‘One-way language exercises Activities’ while "Real-Life Skills Task Activities" were utilized least frequently. The Pearson correlation coefficients revealed a significant positive correlation among the three roles of EFL teachers and their use of classroom activities. This finding highlights the interconnectedness between teacher effectiveness and the utilization of instructional activities in English language teaching. However, there are areas within the teachers' roles that require improvement.